Univerzitetni kampus v 20. stoletju - Giliberti, Marco (Urbani izziv, 2011)
After the Civil War, when socio political reorganisation was urgently needed, American universities contributed to the process of re establishing the internal equilibrium of power within the nation. Thus an attempt was made to reinforce the political parties and develop regions as politically discrete territorial entities that were relatively manageable. In the twentieth century the effect of this policy of local centralisation at the regional level, in conjunction with the opportunity offered by the need to develop more effective city governance, was translated into the awareness that a major contribution of academia to politics is to help re establish the parameters ofgovernability for the entire country. With the goal of documenting and exploring some key relations between campus plans and city planning in Chicago, this paper illustrates a number of campus plans and planning strategies in which "the city" can be thought of as a metonym for the entire society. Nexuses between campus and city planning can be revealed from the creation of the campus of the University of Chicago in 1890 to the first half of the 1960s.
Keywords: naselja; United States of America; univerze; urbanistično planiranje; ZDA